The Effect of Social Media Regulatory Content Law in Indonesia - Hidayat, Taufik; Mahardiko, Rahutomo (Journal of Telecommunications and the Digital Economy, 2020)
Nowadays, information technology (IT) has been used widely in the world. People use IT in their jobs and get the latest information about everything that happens in the world. Therefore, IT has a big impact on peoples’ lives. Information can be found easily in a news portal, social media, and a search engine. This study used social media WhatsApp, Telegram, Facebook, and Instagram as the primary sources. In using social media, people can share positive (news, current research) or negative (hoax) information. Unfortunately, messages can be shared without verifying their truthfulness. Many people have used social media to share fake news and bullying. Hong Kong, France, Indonesia and Venezuela are examples of countries where a hoax has become the part of peoples’ lives. In Indonesia, the government created a Constitutional Law (CL), Undang-Undang Informasi dan Transaksi Elektronik (CL of Information and Electronic Transactions), to regulate responses to negative information and filter this kind of information. This paper analyses the effect of social media regulatory law and hoax news on social life. The results of this study show that the Indonesian CL could be useful to regulate the use of social media in other countries.